Preliminary evaluation of a multipass strategy in abrasive waterjet machining of an alloy UNS A92024. - Bañón-García, Fermín; Gómez Parra, Álvaro; Sambruno, Alejandro; Mayuet, Pedro Francisco (My University, 2023)
Abrasive waterjet cutting is a valuable method for removing material without causing thermal damage, making it suitable for machining materials of different thicknesses and minimising waste. However, machining thicker materials requires higher flow rates and pressure, resulting in increased energy consumption and surface defects that increase costs. This study proposes a multi-pass strategy to improve the performance of abrasive waterjet machining. The study aims to investigate the impact of the number of passes on the efficiency of machining a thick UNS A92024 alloy. Surface integrity will be evaluated from two perspectives: macrogeometry (such as machining depth and taper) using image processing, and microgeometry (surface roughness). The study will also analyse the relationship between the number of passes and traverse speed to identify the optimal combination and develop a predictive model to enhance overall process performance.
Keywords: Aluminio - Aleaciones; AWJM; Waterjet; Kerf